(untitled) (The International Journal of Educational Sciences and Arts, 2023)
This study seeks to clarify the mutual and interrelated relationship between the semantics, change and development of words, and to clarify the psychological factor that surrounds the human being in his different attitudes and linguistic contexts in life, which pushes him to express his opinions in specific linguistic or non-linguistic patterns, by clarifying the psychological dimension in the transformation of semantics in the structure of the Emirati literary text in the light of the poem (The Story of Moses) by the poet Karim Maatouk; Text context. The study adopts the descriptive analytical approach that describes and interprets linguistic phenomena. The study revealed some results, the most important of which are: The poem (The Story of Moses) by the Emirati poet Karim Matouk carries many psychological connotations that fall under the social, cultural, national, religious and other semantic fields, and the words in the text have acquired new psychological connotations different from their lexical meanings, which indicates the impact of the context in giving the word its psychological connotation, and the psychological significance of the words had a role in revealing the poet’s feelings and emotions in the text; He lives between the beautiful memories of the past and the challenges of the bitter present, and one of the socio-psychological issues conveyed by the poet is the desire for male offspring, through the story of Laila with her husband, and he transferred this psychological experience to us by creating a psychological environment derived from linguistic words.